Connecting practices - Shove, Elizabeth, 1959- author.
1 online resource (xii, 140 pages).
Keywords: Connecting Practices develops a distinctive method of conceptualising significant trends and global issues including environmental sustainability and inequalities in wealth and health, arguing that these are outcomes of the ways in which social practices interact and combine across space and time. Engaging with the question of how connections are made between practices and how past and present combinations make some futures more likely than others, this book brings practice theory to bear on large problems in society. Richly illustrated with examples from the spreading of germs to the history of shipping containers, this powerful analysis of how societies hang together and how they change will appeal to scholars and students of sociology and social theory.